Barriers in Access to Pharmaceutical Care in Greece: The Case Study of the Out-of-Hospital Management of Patients With Acute Asthma - Konstantakopoulou, Olympia; Kaitelidou, Daphne; Economou, Charalampos; Charalambous, Giorgos (Frontiers in Public Health, 2018)
Aim: The objectives of this study were to evaluate the effectiveness of information and administrative assistance regarding patient adherence to asthma guidelines and investigate the nature of the barriers in access to pharmaceutical care in Greece based on the case study of the out-of-hospital management of patients with acute asthma. Materials and Methods: The sample of the study consisted of 100 patients with acute asthma who visited the Emergency Department of a General Hospital of Athens. A comparative cross-sectional study using convenience sampling was conducted during October 2014 and June 2015 regarding the adherence to the follow up. Results: Patients who complied with the follow up visit constituted 61% of the total sample (82% of the patients from the intervention group and 40% from the control group) and for those for whom the follow up visit had been scheduled by the researchers had been compliant with the physician's instructions more often than patients for whom the follow up had not been scheduled by the researchers (OR = 8.2, 95%CI = 2.9–23.2). Patients with increased hospitalization days during the previous year and who did not consume the appropriate medication prescribed for asthma due to lack of a prescription, visited the ED more frequently than the rest of the patients (OR = 271.47, 95%CI = 14.53–5070.8). More than one out of three patients (36.4%) reported that they had not bought their asthma medications because they had no prescription while almost one out of five stated that they had purchased their medications but had used them with savings in doses. Patients who had not taken their asthma medication due to lack of prescription, visited more than once the ED, resulting in non-admission, when compared to patients who had a prescription for their medications. (OR = 3.5, 95%CI = 1.3–9.3). Discussion–Conclusions: Out-of-hospital management of asthma in Greece presents significant gaps and shortcomings, mainly due to important unresolved issues regarding availability, accessibility and use of services. The findings of the present study confirm the cause-effect relationship between ineffective out-of-hospital management of asthma and the increase in the frequency of the use of hospital emergency departments, resulting in an increase in health costs.